The Shifting Role of Value-Added Tax (VAT) as a Media Policy Tool: A Three-Country Comparison of Political Justifications. Issue 2 (2nd April 2016) - Ots, Mart; Krumsvik, Arne H.; Ala-Fossi, Marko; Rendahl, Pernilla
Abstract : Media policy schemes around the world are seemingly shifting character. As budgets for direct subsidies are under increasing pressure, the role of indirect tools, such as tax reductions, are growing in relative importance. This article explores the political justifications of value-added tax (VAT) as a media policy tool, and how longitudinal shifts indicate broader changes in the media systems. Based on a document analysis of newspaper VAT development in three countries with similar historical policy models—Finland, Sweden and Norway—the article identifies and describes the dynamics between four major policy positions; transparency, pluralism, harmonisation and financial austerity.